2020
DOI: 10.1002/slct.202003658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Performance Evaluation of Na(2‐x)LixFeP2O7 (x=0, 0.6) Hybrid Cathodes

Abstract: This study reports hybrid cathodes formation by cation substitution in which Li+ substitution has been considered for Na+ in the structure of Na(2‐x)LixFeP2O7 (x=0, 0.6) to form Na1.4Li0.6FeP2O7 cathodes. Na(2‐x)LixFeP2O7 (x=0, 0.6) cathodes were synthesized using the solid‐state synthesis technique and characterized by various methods. The structural analysis (XRD, FE‐SEM) indicates that the submicron‐sized, phase pure, and crystalline materials having irregular morphology have been developed. Moreover, Li+ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Reproduced with permission. [ 98 ] Copyright 2020, John Wiley and Sons. e) Crystal structure of Na 3.12 Fe 2.44 (P 2 O 7 ) 2 .…”
Section: Progress Of Fe‐based Polyanion Oxide Cathodes For Sodium‐ion...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 98 ] Copyright 2020, John Wiley and Sons. e) Crystal structure of Na 3.12 Fe 2.44 (P 2 O 7 ) 2 .…”
Section: Progress Of Fe‐based Polyanion Oxide Cathodes For Sodium‐ion...mentioning
confidence: 99%
“…4 Li 0.6 FeP 2 O 7 , its electrochemical performance is inferior to that of Na 2 FeP 2 O 7 , which may link to the lattice distortion induced by Li-ion's smaller radius (Figure 4d). [98] Zhao and colleagues investigated the influence of B doping, and they discovered that Na 2 Fe 1.95 B 0.05 O 7 /C composite in monoclinic P2 1 /c displayed an initial reversible capacity of 74.8 mAh g -1 , which is much higher than the 66.2 mAh g -1 of Na 2 FeP 2 O 7 /C without B doping. [99] Mg-doped Na 2 FeP 2 O 7 enhanced the cycling stability and rate capability, where the initial reversible capacity of Na 2 FeP 2 O 7 doped with 5% Mg was 90 mAh g -1 at 0.1 C and did not degrade noticeably after 2000 cycles at 9 C. [100] From the synthesis perspective of different sodium sources, Zheng et al found that Na 2 FeP 2 O 7 powder synthesized from sodium dihydrogen phosphate had a better performance, which showed a reversible capacity of 81.0 mAh g -1 at C/10, about 83.5% of the theoretical capacity.…”
Section: Sodium Iron Pyrophosphatesmentioning
confidence: 99%
See 1 more Smart Citation